NEET Strategies in Post-Recession Ireland: Reflections on the Importance of Connecting Formal and Non-Formal Educational Supports - Flynn, Paul (Calitatea Vieții, 2021)
In the aftermath of the 2007−2008 global economic crisis, Ireland had one of the highest unemployment rates in the OECD for those aged between 15−25 years. An over-dependence on the construction and agriculture sectors (used to absorb early school leavers into related apprenticeship programmes) was exposed. Consequently, a reassessment of the challenges this demographic faced informed the development of a suite of targeted responses. This paper reflects on three distinct, although interrelated, areas where strategies which impacted upon NEETs were actioned in Ireland between 2007 and 2019. These are: formal education; non-formal education and training; and, establishing the voice of those most impacted (i.e., NEETs and potential NEETs), as central to the success of emergent and future responses.